Assessment of patient admission outcome at Sulaimani's Intensive Care Unit General Teaching Hospital in 2013: A retrospective study - Kadir, Farida A.; Azize, Pary M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Measuring how many people died each year and why they died along with the assessment of the diseases and the injuries that affected the population, is important for the effectiveness of the country's health (WHO, 2005). This study has been done in order to assess the frequency of the patient's characteristics, reasons and outcome of admission patients in the Sulaimani's Intensive care Unit that determine the type of diseases for hospitalized patients. Information was obtained from the patients’ medical records including (age, gender, occupation, patient's outcome, residency and disease type). The records of 655 hospitalized patients with medical diseases were analyzed from January 2013 to December 2013. Males represented 52.5% and females 47.5% of them. The most affected age groups were 61-70 followed by 71-80. Out of the total, 60.9% of those discharged from hospital were alive, while, 39.1% of them were deceased. Respiratory diseases were the most common cause of admission (22.0%), followed by cerebral disease (20.3 %.), blood disease (13.9%) and heart diseases (13.1%); these were having the highest frequency among hospitalized patients. In Sulaimani, cerebral diseases, respiratory diseases, renal and heart diseases were the more prevalent leading causes of death
Keywords: Hospital admissions; retrospective studymodel; Intensive Care Unit; cerebral disease; heart disease